2014
DOI: 10.1038/srep05359
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent threat: toxicity of light stick attractors used in pelagic fishery

Abstract: Light sticks (LS) are sources of chemiluminescence commonly used in pelagic fishery, where hundreds are discarded and reach the shores. Residents from fishing villages report an improper use of LS contents on the skin. Given the scarce information regarding LS toxicity, the effects of LS solutions in cell cultures were evaluated herein. Loss of viability, cell cycle changes and DNA fragmentation were observed in HepG2 cell line and skin fibroblasts. A non-cytotoxic LS concentration increased the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…After a single day of operation, thousands of spent lightsticks are discarded at sea and constitute a potential toxicant to marine flora and fauna (Poisson et al, 2010). For instance, $7000 discarded lightsticks were collected within 90 km of the northern coast of Bahia State, Brazil (Oliveira et al, 2014). This highlights the fact that fishing operations using lightsticks contribute to the risk of plastic waste (Oliveira et al, 2014).…”
Section: Plastic and Litter Effectsmentioning
confidence: 99%
“…After a single day of operation, thousands of spent lightsticks are discarded at sea and constitute a potential toxicant to marine flora and fauna (Poisson et al, 2010). For instance, $7000 discarded lightsticks were collected within 90 km of the northern coast of Bahia State, Brazil (Oliveira et al, 2014). This highlights the fact that fishing operations using lightsticks contribute to the risk of plastic waste (Oliveira et al, 2014).…”
Section: Plastic and Litter Effectsmentioning
confidence: 99%
“…At the same time, dimethyl phthalate (DMP), diisobutyl phthalate (DIBP), butyl benzoate, butyl 2-ethylhexyl phthalate, diethyl phthalate (DEP); monomethyl phthalate, phthalic anhydride, 1-pentanol; tert-butyl isopropyl ether, n-butyl acetate, butyl butanoate, methyl benzoate, butyl methyl phthalate, benzenesulfonic acid 4-methyl butyl ester, t-butyl hydrogen phthalate, butyl cyclohexyl phthalate, and mono-2ethylhexyl phthalate and trichlorosalicylic acid content were identified in the lightsticks ampoules (Araújo et al 2015). According to Oliveira et al (2014), who analyzed the same samples from discharged lightsticks in the beaches of Costa dos Coqueiros, collected by the NGOs Global Gargabe and Capitães da Areia, identifying in the internal solution: hydrogen peroxide; rubrene (5, 6,11,12-tetraphenylnaphthacene; di-n-butyl phthalate, bis (2,4,6-trichlorophenyl) oxalate (TCPO) and 9,10-diphenylanthracene (DPA); and external solution: dimethyl phthalate and sodium salicylate. This compound group was known for its high toxicity in tests with aquatic organisms, like marine crustaceans, mysids, fairy shrimps, amphipods, and harpacticoid copepods (Mayer & Sanders 1973, Lindén et al 1979.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in distant places, local populations collected lightsticks from the beaches and tried to use the tube content as suntan lotion or for treatment of vitiligo and even mycoses (Cesar-Ribeiro & Palanch-Hans 2010, Cesar-Ribeiro et al 2017. After drifting to the shore, elevated temperatures and solar irradiation indicated the presence of reactive electrophiles and increased cyto and genotoxic potential in human cells forming mutagenic lesions (Oliveira et al 2014). Therefore, we investigated the toxicity of lightsticks collected on Bahia beaches (Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…Living Resour. 29, 402 (2016) (Alessandro and Antonello, 2010;Berkeley et al, 1983;Bigelow et al, 1999;Bromhead et al, 2012;de Oliveira et al, 2014;Gless et al, 2008;Hazin et al, 2005;Ivar do Sul et al, 2009;Lohmann et al, 2006;Pinho et al, 2009;Poisson et al, 2010;Santos et al, 2009;Wang et al, 2007) Prohibition of wire leaders (only nylon allowed) SWO: 19 TUN: 19 SHK: 11…”
Section: Mitigation Measures For Longline Fisheriesmentioning
confidence: 99%
“…The first measure may have economic implications and encounter resistance from those fleet segments for which sharks are an economically important catch or bycatch. Chemical light-sticks have been shown to negatively impact the environment (Ivar do Sul et al 2009;Pinho et al 2009;Santos et al 2009;de Oliveira et al 2014) and increase the probability of catching sharks (Bigelow et al 1999) and sea turtles incidentally (Lohmann et al 2006).…”
Section: The Paucity Of New Solutions For Longline Gears Targeting Tumentioning
confidence: 99%